WOMEN’S FREEDOM IN ALICE HOFFMAN'S THE RED GARDEN - Fanani, Abu; HARDIYANTI, FANNY NANDA; AMIQ, AMIQ (Lingustic, Literature and English Education, 2022)
This article analyzes women’s freedom in Alice Hoffman's The Red Garden. There are four characters analyzed, namely, Hallie Brady, Mary Starrs, Emily, and Hannah Partridge. Using the theory of liberal feminism as well as descriptive and dramatic method, the researcher finds that all the characters mentioned above gets their freedom through their efforts, respectively.